2018
DOI: 10.1038/s41467-018-06963-y
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium adhesin P110 binds sialic-acid human receptors

Abstract: Adhesion of pathogenic bacteria to target cells is a prerequisite for colonization and further infection. The main adhesins of the emerging sexually transmitted pathogen Mycoplasma genitalium, P140 and P110, interact to form a Nap complex anchored to the cell membrane. Herein, we present the crystal structures of the extracellular region of the virulence factor P110 (916 residues) unliganded and in complex with sialic acid oligosaccharides. P110 interacts only with the neuraminic acid moiety of the oligosaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 67 publications
4
58
0
Order By: Relevance
“…1). The first transmembrane region (spanning the N-terminus), and the last transmembrane region (spanning the C-terminus) have been identified in previous studies of P1 32,36,66 , and a P1 paralog of Mycoplasma genitalium 73 . The glycosaminoglycan binding sites consist of reiterated copies of positively charged amino acids that are likely to be important in interactions with sulphated derivatives of heparin and heparan sulfate.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…1). The first transmembrane region (spanning the N-terminus), and the last transmembrane region (spanning the C-terminus) have been identified in previous studies of P1 32,36,66 , and a P1 paralog of Mycoplasma genitalium 73 . The glycosaminoglycan binding sites consist of reiterated copies of positively charged amino acids that are likely to be important in interactions with sulphated derivatives of heparin and heparan sulfate.…”
Section: Resultsmentioning
confidence: 84%
“…, and transmembrane domains (TmD, yellow boxes, TmD 1 predicted by TMpred 66 , TmD 2 previously predicted 32 , TmD 3 previously predicted 36 , and TmD 4 previously predicted in a P1 paralog 73 ) are shown within the black bar. Putative transmembrane domains and the location of 15 subregions of P1 (grey 'RP' boxes) expressed as recombinant proteins from an earlier study 55 are shown.…”
Section: Immunoblot Of M Pneumoniae Cell Lysates Using Anti-p1 Serummentioning
confidence: 99%
“…The adhesin complex in M. genitalium is also composed of a dimer of heterodimers constructed by P110 and P140, the homologs of P1 adhesin and P90, respectively (53). P110 has a binding site for SOs, so one adhesin complex binds two SOs (31). The adhesin complex of M. gallisepticum is assumed to have two binding sites for SOs because it is composed of CrmA and GapA, the homologs of P110 and P140, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…P90 is encoded in tandem with P1 adhesin and is cleaved from another protein, P40, for maturation (29, 30). A recent study shows that the homolog of P40/P90 in M. genitalium , P110, has a binding pocket of sialylated oligosaccharides (SOs) (31), which are binding targets for Mycoplasma infection and gliding. The mechanism of the gliding motility has been proposed as an ‘inchworm model,’ in which a cell catches SOs on solid surfaces through the adhesin complexes and is propelled by the repetitive extensions and retractions of the internal core (3, 7, 8).…”
Section: Introductionmentioning
confidence: 99%
“…In mycoplasmas, cytoadhesins are often involved in several key biological functions. Beside their crucial roles in cell adhesion, they are also important for invasion, colonization, and dissemination within the hosts [47]. This prompted us to test the translocation of strain HB0801 across epithelial cell monolayers.…”
Section: Discussionmentioning
confidence: 99%